2021
DOI: 10.3390/molecules26164951
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Propionic Acid Inducing Cell Death in Cervical Cancer Cells

Abstract: Recent studies found that short-chain fatty acids (SCFAs), which are produced through bacterial fermentation in the gastrointestinal tract, have oncoprotective effects against cervical cancer. The most common SCFAs that are well known include acetic acid, butyric acid, and propionic acid, among which propionic acid (PA) has been reported to induce apoptosis in HeLa cells. However, the mechanism in which SCFAs suppress HeLa cell viability remain poorly understood. Our study aims to provide a more detailed look … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Anticancer effects of SCFAs, especially butyrate, is well documented; its proper concentrations reduce proliferation and induce programmed cell death in CRC and other cancer cells [ 54 ]. Propionic acid can induce ROS generation, MMP depletion, and cell death (autophagy) in HeLa cells [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anticancer effects of SCFAs, especially butyrate, is well documented; its proper concentrations reduce proliferation and induce programmed cell death in CRC and other cancer cells [ 54 ]. Propionic acid can induce ROS generation, MMP depletion, and cell death (autophagy) in HeLa cells [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…41 Similarly, Pham et al reported similar results in a study that compared the viability of cervical cancer cell lines (CaSki, SiHa, and HeLa cells) with normal cells BEAS-2B after treatment with propionic acid at a differential concentration. 42 The volatilome of HNC in saliva samples showed lower levels of propionic acid in HNC patients compared with healthy controls. 39 In our study, we found that propionic acid levels were significantly lower in ST users compared to ST nonusers, which is in line with previous reports assuming that ST alters the gut microbiota and depletes the body of beneficial organic acids, which can lead to various disorders.…”
Section: Discussionmentioning
confidence: 95%
“…Propionic acid has been shown to reduce fatty acid accumulation in the liver and plasma, decrease food intake, have immunosuppressive effects, and increase tissue insulin sensitivity . Studies have revealed that propionic acid has anticancer properties, and its levels have decreased in various types of cancer, such as HNC and cervical cancer. , In their caecal contents, rats exposed to cigarette smoke showed a significant decrease in SCFA, i.e., propionic acid, butyric acid, and valeric acid . This result suggested that smoking cigarettes may alter the gut environment and affect the gut microflora in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, metabolomics has also played a key role in characterizing SCFAs and their antitumor effects, especially in colorectal cancer [203,204]. As shown through a number of studies, SCFAs, such as butyric acid, acetic acid, and propionic acid, can act as histone deacetylase inhibitors or as autophagy/apoptosis promoters [204,205]. The production of SCFAs is largely driven by gut microbiota which convert dietary fiber into these anti-oncogenic fatty acids.…”
Section: Connecting the Multiple Views Of Cancer Through Metabolomicsmentioning
confidence: 99%